DEVELOPMENT OF THE FACTUAL, CONCEPTUAL AND PROSEDURAL QUESTIONS ON THE MOVING MATERIALS OF CLASS VIII SMP - Iskhaq, Ainul; Wijayadi, Andri Wahyu (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2024)
The students' knowledge of Physics Science material, especially in the subject of the motion of objects, is still below the expected KKM standard. Motion material is the basis or prerequisite for understanding further science material related to object motion material in class VIII to class IX. So far, there has never been an assessment related to the abilities of students' knowledge dimensions. This research focuses on assessing faktual, konseptual and prosedural knowledge according to the IC issued by the Ministry of Education and Culture. This type of research is development research using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The purpose of this research is to describe the process of developing factual, conceptual and prosedural knowledge questions and to find out the dimensions of students' knowledge on the material motion of objects. The data obtained in this research is in the form of qualitative and quantitative data. Empirical validity analysis of 14 multiple-choice items and essays yielded the characteristics of the questions consisting of validity of 13 (92.8%) valid items, reliability of items with Cronbach's alpha 0.630 on 8 multiple-choice items and Cronbach's alpha 0.638 on 5 essay items greater than the r table value of 0.6, the level of difficulty is 64,3% items with moderate criteria, the discriminating power is 28,57% very good, 28,57% good questions, and 28,57% sufficient.